Islamic Educational Institutions as Entrepreneurial Organizations: Lembaga Pendidikan Islam sebagai Organisasi Kewirausahaan - Ikhwan Abdillah; Abdullah (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2025)
This study presents a conceptual analysis of Islamic educational institutions as entrepreneurial organizations, addressing the limitations of predominantly normative and administrative Islamic education management approaches, which adequately account for organizational adaptability, innovation, and sustainability. Through a critical literature synthesis, the study develops a conceptual model positioning entrepreneurship as a strategic organizational framework aligned with Islamic values, integrating strategic orientation, managed innovation capacity, and institutional sustainability. Findings indicate that an entrepreneurial orientation functions as a strategic guiding logic, enabling institutions to regularly respond to environmental changes without compromising normative principles and educational objectives. The proposed model bridges organizational entrepreneurship theory and Islamic education management practices, offering a conceptual The proposed model bridges organizational entrepreneurship theory and Islamic education management by conceptualizing entrepreneurship as a strategic organizational logic rather than an auxiliary economic activity. The study’s main contribution lies in demonstrating that an entrepreneurial orientation—integrated with adaptive governance structures and Islamic value-based organizational culture—can strengthen institutional innovation and sustainability without compromising educational missions. By positioning Islamic educational institutions as value-driven entrepreneurial organizations, this study extends organizational entrepreneurship theory to non-profit, faith-based contexts and enriches Islamic education management scholarship with a strategic and adaptive perspective. Furthermore, it outlines clear directions for future research, including empirical validation of the model, the development of value-based operational indicators, and comparative analysis across institutional setting.